Lifting Eighth-Grade Students' Recount Text Writing Skills through Mind Mapping - Asror, Khozinatul; Fadhilawati, Dian; Aini, Miza rahmatika (Academy of Education Journal, 2024)
This research was conducted at SMP Al Kamal Wonodadi Blitar to lift the personal recount writing skills of eighth-grade students, totaling 29 students, especially on the topic of personal recount by integrating mind mapping. The researchers implemented classroom action research based on Kemmis and Taggart's model with four main steps: planning, acting, observing, and evaluating, as well as reflecting. Data were collected through tests. The results of this study showed a significant transformation in students' writing abilities after using mind mapping, increasing from 55.66 in the pre-test to 81.14 in the post-test. This improvement involved various aspects of writing such as grammar usage, vocabulary selection, idea development, content quality, and mechanical accuracy in the context of personal recount texts. Based on these results, the researchers recommend that English teachers integrate mind mapping as an alternative tool to develop students' writing skills.